Wirtschaftliche Zwänge - Horst Siebert (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1984)
The paper discusses the role of restraints in the economic System. The constraints may relate to different agents of the economic-system so that one may envision the economic system as a Set of hierarchical constraints with each layer.of constraints applying to a more disaggregated level of constraints. Each economic system is confronted with the problem of transforming higher level type constraints into constraints for lower level agents. The paper analyzes mechanisms through which global restraints can be transformed into lower level checks for decentralized autonomous units. Markets and property rights are important vehicles for transforming global constraints Equity considerations may induce politicians to intervene into the process of signaling global restraints to the decentralized units. Then the signaling of restraints is likely not to be incentive compatible. Restraints may be violated and more severe restraints may come into being. Moreover, the politician has an incentive to Camouflage the opportunity costs of violating restraints.
Keywords: 330